Managing air quality in Suva, Fiji - Isley, Cynthia Faye; Nelson, Peter F.; Taylor, Mark P (European Journal of Sustainable Development, 2016)
Increased vehicular traffic and industry, added to widespread burning of wastes, contribute to Suva’s fine aerosol particle air pollution (PM2.5); particularly aerosol black carbon (BC). As well as potential improvement of health and amenity on a local scale, better management of air quality has implications for global atmospheric warming. Diesel vehicle emissions contribute 100 ± 30 t of PM2.5 to Suva’s air annually, including up to 75 t BC. A survey of 125 Suva households, in 2014, showed that most Suva residents burn a portion of their household waste, contributing 50 ± 14 t PM2.5 per year, including between 2.1 t and 17 t BC; a combustion activity that is largely unnecessary. The estimated specific forcing potential due to Suva’s black carbon emissions is between 50.5 TJ and 114 TJ annually. Emissions reductions may be achieved through various means, including alternative waste disposal practices and changes in fuel types and in fuel sulphur contents. Key words: combustion emissions, PM2.5, black carbon, emission estimation